(untitled) (Kronika Bydgoska, 2014)
Konrad Pałubicki was born on March 16, 1910 in the village of Dziembówko, Piła area. The Pałubicki family settled down in Bydgoszcz in 1920. He graduated from the State Humanist Middle School in Bydgoszcz. He started piano lessons at age 17 with Jolanta Bylczyńska. He graduated from the Poznań University with a degree in musicology. In 1945, he returned to Bydgoszcz and started working in the state secondary school of music. He participated in all cultural initiatives, not only related to music. In 1946, he won the Bydgoszcz bugle call competition organized during the celebrations of the 600th anniversary of Bydgoszcz. Konrad Pałubicki was first and foremost a composer. The series of seven songs entitled Reflections was written in 1976, first in a version with female vocal and piano, and later with female vocal accompanied by an instrumental ensemble. We should look for the background of the series in existential dilemmas of the artist related to transience. Songs entitled I Am Searching, Flight, What is Flower, I Wish the Morning Would Just Stay, Take Me in Your Arms, Butterfly, Is it My Afternoon oscillate thematically around feelings of hope, inevitability of fate, and death. Konrad Pałubicki’s Reflections are the type of vocal lyric written over the years of work of the composer.